Significance of media and the understanding of 1Malaysia concept - Abdullah, Amini Amir; Mistar, Fahmi Azar (2013)
This study is about the medium used by the youth in Malaysia in obtaining information on the 1Malaysia Concept. The information gained in this study also revealed the understanding of youth on the 1Malaysia Concept. This study also explored the level of Malaysian youth’s understanding of the 1Malaysia Concept according to race (Malay, Chinese, Indian and others) and identified mediums and methods used by youth in understanding the 1Malaysia concept. Altogether, 1,600 youth were selected as respondents for this study. 100 respondents were selected from each of the states and the three Federal Territories. The respondents were selected via the convenience sampling method. The selected samples represent youth from diverse races and both genders. In this matter, no specific basic procedure is applied in selecting the races and genders of respondents. Information was obtained through questionnaires answered by the respondents. The IBM Statistical Package for Social Science (SPSS) version 20.0 was used to analyses data gathered via the questionnaires. Two questions were given to get complete inputs on most frequently mediums used by Malaysian youth to obtain information on the 1Malaysia concept, as well as mediums that are most effective in understanding the 1Malaysia concept. Respondents were required to mark unlimited alternatives that are given in the questionnaires. Eleven (11) mediums were used by youth to obtain information on the 1Malaysia concept. They were the television, Internet, newspapers, radio, bulletins, magazines, books, speeches, blogs, newsletters and others. Most of the respondents (83.9%) stated that the television is most frequently used followed by the Internet (67.8%), newspapers (63.7%), radio (50.1%), bulletins (40.4%), magazines (30.9%), books (29.9%), speeches (20.3%), blogs (22.8%), newsletters (7.8%) dan others (1.2%). On the most effective mediums in understanding the 1Malaysia concept, majority of the respondents (77.1%) stated that the television as being the most effective, followed by the internet (63.6%), newspapers (50.9%), radio (43%), bulletins (36.1%), books (25.8%), magazines (25.1%), speeches (23.8%), blogs (20.1%), newsletters (7.9%) and others (1.8%). Overall, the level of Malaysian youth’s understanding of the 1Malaysia concept is high.